Culinary MSMEs Fail to Protect Their Brands Due to Delays in Registration Decision Number 79/Pdt.Sus-HKI/Merek/2024/PN Niaga Jkt.Pst - Naftalia Prasetya; Siti Zahrania Maqdis (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector are a key pillar of the Indonesian economy; however, many business owners neglect the legal protection of their intellectual assets, particularly trademarks. This paper examines the legal impact of the failure of culinary MSMEs to register their trademarks in a timely manner, which leads to disputes and financial losses. Using a qualitative case study of the Commercial Court Decision Number 79/Pdt.Sus-HKI/Merek/2024/PN Niaga Jkt.Pst, this research analyzes how Indonesia's trademark law system, which adheres to the first-to-file principle, grants supremacy of rights to the first registrant. The analysis shows that exclusive rights to a trademark arise from registration, not from prior use. The court rejected the arguments of